2002
DOI: 10.1046/j.1471-4159.2002.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective modifications in the nucleus accumbens of dopamine synaptic transmission in rats exposed to chronic stress

Abstract: Stressful events are accompanied by modifications in dopaminergic transmission in distinct brain regions. As the activity of the neuronal dopamine (DA) transporter (DAT) is considered to be a critical mechanism for determining the extent of DA receptor activation, we investigated whether a 3-week exposure to unavoidable stress, which produces a reduction in DA output in the nucleus accumbens shell (NAcS) and medial prefrontal cortex (mPFC), would affect DAT density and DA D 1 receptor complex activity in the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 49 publications
(56 reference statements)
3
24
0
2
Order By: Relevance
“…This finding is in line with studies that showed a decrease in basal extracellular dopamine levels in the NAcc shell [22,54] , a decreased number of dopamine transporter binding sites [54] as well as an increase in D 1 receptor-specific radioligand binding and V max of D 1 agonist-stimulated adenylyl cyclase in the NAcc, but not in the striatum, of animals submitted to chronic stress [54,55] . That this is a regionally specific effect is suggested by findings that neither acute nor chronic stress changed D 1 and D 2 receptor expression levels in the amygdala [56] .…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in line with studies that showed a decrease in basal extracellular dopamine levels in the NAcc shell [22,54] , a decreased number of dopamine transporter binding sites [54] as well as an increase in D 1 receptor-specific radioligand binding and V max of D 1 agonist-stimulated adenylyl cyclase in the NAcc, but not in the striatum, of animals submitted to chronic stress [54,55] . That this is a regionally specific effect is suggested by findings that neither acute nor chronic stress changed D 1 and D 2 receptor expression levels in the amygdala [56] .…”
Section: Discussionsupporting
confidence: 91%
“…Levels of DA, the associated metabolites dihydroxyphenylacetic acid (DOPAC) and homovanillic acid (HVA), serotonin (5-HT), and the intracellular DA turnover (DOPAC/DA) were determined in frontal cortex, nucleus accumbens, and frontal cortex using methods established in our laboratory (Thiruchelvam et al 2000) and measured at a sensitivity of 2 nA for striatum and frontal cortex and 1 nA for nucleus accumbens. These neurotransmitters have demonstrated sensitivity to Pb (CorySlechta et al 1992(CorySlechta et al , 1996Kala and Jadhav 1995;Pokora et al 1996) and to stress (Armando et al 2003;Bland et al 2003;ChouGreen et al 2003;Finlay and Zigmond 1997;Hanley and Van de Kar 2003;Mangiavacchi et al 2001;Scheggi et al 2002). DA and 5-HT play key roles in the brain regions examined, which include components of both the nigrostriatal and mesolimbic DA systems, thus also allowing some assessment of specificity of effects.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, it has been reported that acute exposure to different forms of stress increases dopamine release in the NAc [73,163]. In contrast, long-term exposure to various unavoidable stress factors decreases dopamine release in the NAc shell [37,38,143]. Furthermore, it has also been reported that mice exposed to escapable foot shock show an increase in dopamine release in the NAc, while those exposed to inescapable foot shock show a decrease in dopamine release in the NAc [22].…”
Section: Dopaminementioning
confidence: 99%
“…Another recent study reported that chronically stressed rats showed a decrease in the number of dopamine transporter (DAT) binding sites, and an increase in the number of D1 binding sites in the NAc shell [143]. In contrast, chronic treatment with antidepressants increased expression of dopamine receptors, including the D2 and D3 types, in the NAc shell [2,86].…”
Section: Dopaminementioning
confidence: 99%